Integrating creative thinking and cultural insights through the anthropological theory of didactics in university algebra - Ontiveros, Yanko Ordóñez; González, Julián Roa; Palencia, José Luis Díaz (Journal of Education and Learning (EduLearn), 2025)
This discussion explored the integration of creative thinking pedagogy and the anthropological theory of didactics in university-level algebra education, emphasizing the importance of understanding the perspectives of both learners and teachers. The work began by highlighting the necessity of considering these viewpoints to create effective and responsive educational experiences. We then focused on designing classroom sessions for algebra, blending creative thinking with cultural and historical contexts. These sessions included applying creative approaches to group theory, exploring algebraic topology through innovative means, and understanding ring theory in practical scenarios like cryptography. Feedback from both learners and teachers was generally positive, with students appreciating the engaging and practical aspects and teachers recognizing the benefits of creative pedagogies. However, challenges in implementation, such as resource constraints and the need for professional development, were also identified. Suggestions for improvement included deeper content exploration, enhanced use of technology, and better alignment of creative teaching methods with assessment strategies.